Dampak Penerapan Pola Asuh Orang Tua Terhadap Karakter Disiplin Siswa SMP N 2 Candiroto Satu Atap - Amalia Adya Pawestri; Natal Kristiono (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
There was a decrease in the character of student discipline due to Covid 19, where students studied online at home. This relates to the application of parenting style applied by parents. The purpose of this research is to find out the application of parenting style, influencing factors and parents' solutions in the formation of students' disciplinary character. This research method is descriptive qualitative. Data collection techniques using interviews, observation and documentation. Data validation techniques use triangulation of sources and techniques as well as data analysis techniques by collecting, presenting, reducing, and drawing conclusions of data. The results of the study show that 1) The application of democratic parenting by parents produces a good disciplined student attitude, with the parenting style applied by parents, the rights and obligations between children and parents are given in a balanced manner 2) Factors that influence the formation of parenting patterns are parental education, the surrounding environment, and the parents' economy. 3) Parents' solution in improving the formation of student discipline character is always teaching discipline to children in their home environment, applying existing rules in the house and giving punishment when children break these rules.